The Effect of Deep Breathing Therapy on the Blood Pressure of Hypertension Patients in Health Centre - Rezkiyah Hoesny; Zainal Alim; Darmawati Darmawati (State Islamic University of Sunan Ampel, 2019)
Hypertension is an increase in persistent blood pressure which can be at risk for cardiovascular diseases. An uncontrolled increase in blood pressure can cause damage to the, heart and blood vessels. The purpose of this study is to analyze the effect of deep breathing therapy on blood pressure in hypertension patients in the work area of Wara Health Centre. The research design used Quasi Experiment, one group pre-test and post-test design, to 22 respondents selected by accidental sampling. Respondent's blood pressure was measured (pre-test), then breathing therapy was carried out for 15 minutes, then the respondent's blood pressure was measured (post-test). This intervention was carried out for three consecutive days for each respondent. The results indicated the average value of systolic blood pressure before deep breathing therapy get the probability value of 0.000 showing 0.000 <0.05 and the average value of diastolic blood pressure before deep breathing therapy get the probability value of 0.000 showing 0.000 <0.05. It can be concluded that there is an effect of deep breath therapy on blood pressure in hypertensive patients in the working area of Puskesmas Wara. It is recommended to apply breath therapy in the treatment of hypertensive patients, carry out training for health workers, cadres, and also families, so that this therapy can be carried out independently by patients at home.